2010
DOI: 10.1080/03069881003600983
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking attitudes among Arab and Jewish adolescents in Israel

Abstract: This study set out to explore the impact of ethnicity, gender, age and subjective well-being on help-seeking attitudes among Arab and Jewish adolescents in Israel. The sample comprised 395 Arab and 360 Jewish 7th-and 11th-grade pupils who were selected from six Arab and six Jewish schools in the north of Israel. The participants completed a self-report help-seeking questionnaire and an inventory measuring subjective well-being. Quantitative analyses testing the research hypotheses revealed that Arab youths wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…One study (Gilat et al . ) revealed that when a member Arab family shows symptoms of mental illness, Arabs usually turn first to family practitioners (33%), followed by family members (21.6%), and then the Sheikh (19%). Only 11% turn to mental health practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…One study (Gilat et al . ) revealed that when a member Arab family shows symptoms of mental illness, Arabs usually turn first to family practitioners (33%), followed by family members (21.6%), and then the Sheikh (19%). Only 11% turn to mental health practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, school consultation may be perceived as a normative act, whereas turning to professional mental health sources, particularly psychologists, may be perceived as stigmatic [11]. Some studies show that adolescents perceive school staff as more acquainted with their lives and as better able to understand their difficulties than mental health professional sources and that students believe school staff will continue to value them despite the disclosure of their weaknesses [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies carried out in Israel have found that more Israeli Arab than Jewish adolescents reported their intention to seek help from teachers and educational counselors [13], and more Israeli Arab adolescents exposed to frequent and severe acts of violence requested help from a mental health professional [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' desire for autonomy and self-reliance is also known to be driving them to solve problems without external aid (Kuhl, JarkonHorlick, & Morrissey, 1997) coupled with their notion that no one could really understand them (Gilat, Ezer, & Sagee, 2010). Seeking help from formal sources is furthermore impaired by the feeling emotionally remote from the help source (Fox & Butler, 2007).…”
Section: Internal Factorsmentioning
confidence: 97%